Incidence of overweight and obesity according to body mass index and lipid profile in Pharmacy and Biochemistry students of the Jorge Basadre Grohmann National University of Tacna, 2016 - Rivera Benavente, Orlando Agustín (2021)
Objective: To determine the incidence of overweight and obesity according to body mass index and lipid profile in Pharmacy and Biochemistry students of the Jorge Basadre Grohmann National University, Tacna. Material and methods: Observational, descriptive and correlational study. Fasting blood sample was taken for laboratory analysis of lipid perfyl and glycemia, and weight and height were evaluated with calculation of body mass index to a non-probabilitic sample of 38 students of Pharmacy and Biochemistry of the Health Sciences Faculty. The data were collected on a data sheet and processed in the statistical software SPSS v19. Descriptive statistics were used for the analysis. The square Chi test was used to establish the relationship between the variables, with a confidence level of 95 % and asymptotic significance of <0.05. Results: The students were 18 to 26 year-old, with an average of 20.7, weight of 62.3 Kg and height of 1.61 m. 26.7 % of women and 25.0 % of men were overweight. According to lipid profile: 5.3 % had high total cholesterol and moderate risk 18.4 %, all normal HDL cholesterol, 26.3 % LDL high cholesterol, 5.3 % had high triglyceride values and 31.6 % mild hypoglycemia. All men had normal values of total cholesterol, HDL and LDL; and all women had normal triglycerides. About physical activity, 26.3 % do little physical activity and 18.4 % do not do any physical activity. No statistically significant differences were found between female and male gender (p>0.05). Conclusion: The incidence of overweight and obesity is more frequent in women, and in their lipid profile have high levels of total cholesterol, LDL cholesterol and triglycerides.